Experimental and numerical study of ventilation cavitation around a NACA0015 hydrofoil with special emphasis on bubble evolution and air-vapor interactions. Issue 3 (8th May 2018) - Yu, An; Luo, Xianwu; Yang, Dandan; Zhou, Jiajian
Abstract : Purpose: This paper aims to gain a clear understanding of the ventilated cavity evolution around an NACA0015 hydrofoil by using both experimental and numerical investigation. Design/methodology/approach: The bubble evolution around an NACA0015 hydrofoil with or without air injection was observed in a water tunnel, and the simulation was conducted using a modified turbulence model and homogeneous cavitation model. Findings: The present simulation method can successfully predict the bubble evolutions around the NACA0015 hydrofoil with or without air injection. Air injection can alleviate the nature cavitation oscillation, and the suppression effect on nature cavitation depends on the air-entrant coefficient. It is confirmed that the air and vapor cavity have the same shedding frequency. It is seen that the air sheet closely attaches to the hydrofoil surface and is surrounded by the vapor sheet. Thus, the injected air promotes vapor growth and results in an increase in the cavity shedding frequency. Further, with a large air-entrant coefficient, the pressure fluctuation is suppressed completely. Originality/value: The new simulation method is adopted to explore the mechanism of ventilated cavitation. The bubble evolutions with and without air injection have been comprehensively studied by experimental and numerical investigation. The effects of air injection on natural cavity oscillations and pressure fluctuations have been revealed in the present study.